Hirao Cross-Coupling Reaction as an Efficient Tool to Build Non-natural C2-Phosphonylated Sugars - Monasson, Olivier; Malinowski, Maciej; Lubin-Germain, Nadège; Ferry, Angélique (Synthesis, 2022)
A range of C2-phosphonylated sugars have been accessed through a palladium-catalyzed Hirao cross-coupling on 2-iodoglycals using trialkylphosphites as phosphorylating reagents. The developed conditions led to the creation of an unnatural C–P bond on sugars and proved to be compatible with diversely protected glycals (acetyl-, benzyl-, PMB-protected) as well as with unprotected substrates. Several monosaccharides and one disaccharide have been synthesized by applying this methodology. Deprotection conditions are also described.
Keywords: phosphonylation; cross-coupling; 2-iodoglycals; palladium catalysis; glycoanalogues